Geminal dianions stabilized by phosphonium substituents - Harder, Sjoerd (Coordination Chemistry Reviews, 2011)
This review summarizes the rapid developments in the chemistry of phosphonium-stabilized group 1 and 2 methandiides, i.e. that of alkali and alkaline-earth metal bis(iminophosphorane)methandiide and bis(thiophosphorane)methandiide complexes. Apart from syntheses, structures and reactivities, also a critical discussion on bonding is given. The group 2 complexes of this type can truly be seen as polar metal carbene compounds with a formally polar double metal-carbon bond. © 2010 Elsevier B.V.